2017
DOI: 10.1088/1755-1315/80/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Flexural Fatigue Strength of Self Compacting Fibre Reinforced Concrete Beams

Abstract: Abstract. This study presents the extensive statistical investigation ofvariations in flexural fatigue life of self-compacting Fibrous Concrete (FC) beams. For this purpose, the experimental data of earlier researchers were examined by two parameter Weibull distribution.Two methods namely Graphical and moment wereused to analyse the variations in experimental data and the results have been presented in the form of probability of survival. The Weibull parameters values obtained from graphical and method of mome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Otras líneas de investigación de especial interés práctico son los hormigones autocompactantes reforzados con fibra de acero y como éstos se comportan a fatiga. Poveda et al [18], analizan el efecto e influencia de la cantidad de fibra y las propiedades mecánicas en el desempeño a fatiga de SFRC autocompactantes. Los resultados de este estudio son consistentes en cuanto a las mejoras en las propiedades mecánicas como en la investigación desarrollada Murali et al [19].…”
Section: Nuevas Líneas De Investigaciónunclassified
“…Otras líneas de investigación de especial interés práctico son los hormigones autocompactantes reforzados con fibra de acero y como éstos se comportan a fatiga. Poveda et al [18], analizan el efecto e influencia de la cantidad de fibra y las propiedades mecánicas en el desempeño a fatiga de SFRC autocompactantes. Los resultados de este estudio son consistentes en cuanto a las mejoras en las propiedades mecánicas como en la investigación desarrollada Murali et al [19].…”
Section: Nuevas Líneas De Investigaciónunclassified
“…In addition, Al-Azzawi et al [20] reported that a uniform fiber distribution can lead to a very high fatigue endurance limit when brass-coated steel fibers were added into the matrix. Compared with the normally vibrated steel fiber reinforced concrete, self-compacting concrete is more attractive [21]. It was shown that adding steel fibers into self-compacting concrete led to higher fatigue strength (two-million cycles) from 62% of the corresponding static strength to 71% compared with the normally vibrated fiber reinforced concrete when steel fiber volume fraction is 1.5% [22].…”
Section: Introductionmentioning
confidence: 99%